Parasopubia (Orobanchaceae): A new species from Uttara Kannada, Karnataka, India - Betageri, Shreyas; Patgar, Vanaja G.; Kotresha, K. (Phytotaxa, 2025)
A species collected from the lateritic plateau of the coastal region of Uttara Kannada district, Karnataka during October-November. After analyzing the species, it is newly described as Parasopubia gorensis sp. nov. with differentiating characters like dwarf nature of habit, leaf with spines, corolla with glands, calyx smaller than ovary, capsule oblate shape half enclosed in calyx, seeds sickle shape. This article describes its illustration, color plate and seed morphometry.